Characterization of Sentani gudgeon, Oxyeleotris heterodon (Weber, 1907) at Sentani Lake, Papua, Indonesia based on truss morphometric - ABINAWANTO ABINAWANTO; EKA DEWI SRIYANI (Society for Indonesian Biodiversity, 2018)
Abinawanto, Sriyani ED, Bowolaksono A. 2018. Characterization of Sentani gudgeon, Oxyeleotris heterodon (Weber, 1907) at Sentani Lake, Papua, Indonesia based on truss morphometric. Biodiversitas 19: 1013-1020. The study concerning the morphometry of Sentani gudgeon (Oxyeleotris heterodon, Weber 1907) was done from August 2016 until April 2017 in Sentani Lake, Jayapura District, Papua Province, Indonesia. The objectives of the study were to find out the diversity of the fish using truss morphometry approach. A total 56 individual sampled from three sampling sites were characterized for their 26 truss morphometric characters. The result showed that there were differences on morphometric characters of Sentani gudgeon. The highest correlation value found in character B2 and D5, which represented the dorsal portion and the tail fin of the fish body respectively. All variables showed significant different between each location (the p-value <c0.05). The canonical diagram resulted of 26 truss morphometric characters illustrated three separated clusters which discriminated the three populations based on sampling sites. A genetic distance analysis among Sentani gudgeon indicated that the fish originated from Putali Village was morphologically closed to the fish population from Sosiri. The truss morphometry technique can be used to identify the diversity of Sentani gudgeon in Sentani Lake.